2009
DOI: 10.1111/j.1600-0625.2008.00806.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased expression of TRPV1 channel in intrinsically aged and photoaged human skin in vivo

Abstract: Transient receptor potential vanilloid type 1 (TRPV1) is activated by various stimuli including capsaicin, heat and acid. While TRPV1 has been localized in the epidermis, little is known about the physiological role of TRPV1 in the skin, especially in skin ageing. In this study, we investigated the effect of acute UV irradiation on TRPV1 expression in human skin and the changes in TRPV1 mRNA and protein in intrinsic ageing and photoageing using human sun-protected (upper inner arm) and sun-exposed (forearm) sk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 35 publications
1
45
0
Order By: Relevance
“…[14][15][16] Furthermore, changes of TRPV1 expression (in human skin) can be detected after UV irradiation. 17 Transient receptor potential V1 mediates heat shock-induced matrix metalloproteinase-1 (MMP-1) expression in human keratinocytes. 18 However, diverse TRPV1 activation mechanisms induced through various (physical) stimuli have not yet iovs.arvojournals.org j ISSN: 1552-5783 been elucidated.…”
Section: Methodsmentioning
confidence: 99%
“…[14][15][16] Furthermore, changes of TRPV1 expression (in human skin) can be detected after UV irradiation. 17 Transient receptor potential V1 mediates heat shock-induced matrix metalloproteinase-1 (MMP-1) expression in human keratinocytes. 18 However, diverse TRPV1 activation mechanisms induced through various (physical) stimuli have not yet iovs.arvojournals.org j ISSN: 1552-5783 been elucidated.…”
Section: Methodsmentioning
confidence: 99%
“…However, photoaged skin of older subjects showed increased expression of TRPV1 mRNA and protein compared with that of the sun-protected skin of the same people. Therefore, the expression of TRPV1 is affected by both the intrinsic aging and photoaging processes (Lee et al, 2009). The increased TRPV1 expression in skin from older people implies that TRPV1 may be related to senile skin symptoms, such as senile pruritus and neurogenic inflammation; therefore TRPV1 has been proposed as an intriguing novel target for the prevention of skin aging and inflammation.…”
Section: B Skinmentioning
confidence: 99%
“…Outside of the CNS, TRPV1-expressing afferents have been reported to be present in different human tissues including vascular smooth muscle, bronchial epithelial cells (Seki et al, 2007), the epidermis (Lee et al, 2009), and the gastrointestinal tract (Yiangou et al, 2001;Chan et al, 2003;Matthews et al, 2004). This suggests other roles for TRPV1 besides nociception (for a full review on the subject, see Fernandes et al, 2012).…”
Section: Transient Receptor Potential Vanilloid 1 Receptor Expresmentioning
confidence: 99%
“…Thus, TRPV1 might be associated with skin infl ammatory responses. Ultraviolet (UV) radiation appears to induce the expression of TRPV1 in human epidermal keratinocytes [ 73 ] ; acute UV radiation increased TRPV1 in human skin, and moreover, TRPV1 expression in sunexposed skin was signifi cantly higher than that in sun-protected skin. They also demonstrated that UV radiation induced matrix metalloproteinase-1 in cultured HaCaT cells [ 74 ] .…”
Section: Pain and Itchingmentioning
confidence: 99%